2007
DOI: 10.1152/ajprenal.00215.2007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed recovery of renal regional blood flow in diabetic mice subjected to acute ischemic kidney injury

Abstract: Ischemic acute kidney injury in experimental diabetes mellitus (DM) is associated with a more severe deterioration in renal function than shown in nondiabetic animals. We evaluated whether the early recovery phase from acute kidney injury is associated with a more prolonged and sustained decrease in renal perfusion in diabetic mice, which could contribute to the impaired recovery of renal function. Perfusion to the renal cortex and medulla was evaluated by laser-Doppler flowmetry in 10- to 12-wk-old anesthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Increased susceptibility of the kidney to ischemic insults has been reported in experimental models of diabetes and in clinical studies involving patients with diabetes (17,25,31,32,47). The mechanisms underlying this susceptibility remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased susceptibility of the kidney to ischemic insults has been reported in experimental models of diabetes and in clinical studies involving patients with diabetes (17,25,31,32,47). The mechanisms underlying this susceptibility remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with insulin prior to the ischemic event reduced ischemic injury whereas administration of insulin after the ischemic insult had no beneficial effect (32). A study in a murine model of type 2 diabetes mellitus (DM) (db/db) also demonstrated an increased risk for ischemic acute renal failure (47). In that study, a delayed recovery of renal blood flow after the ischemic event was noted in the diabetic mice.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…We focused on ischemia-reperfusion renal injury, because it drastically depresses capillary renal blood flow in the postischemic period in obese-diabetic mice and, subsequently, reduces renal blood flow (44). Renal hemodynamic and inflammatory changes may interact and worsen renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…After release of renal artery occlusion, total renal blood flow (RBF) is restored to baseline levels within minutes followed by a subsequent decline in RBF, which takes place over several hours [29, 30] [31-33]. Methods that discriminate regional blood flow in the kidney, suggest that outer medullary RBF undergoes an earlier and more significant impairment relative to whole kidney RBF [32-35].…”
Section: Hemodynamic Changesmentioning
confidence: 99%